個人-組織の価値観が校長のリーダーシップに及ぼす影響(III 研究報告) - 露口, 健司 (Bulletin of the Japan Educational Administration Society, 2004)
The purpose of this paper is to examine the prescriptive factors of a principal's leadership from the viewpoint of values leadership theory and the values fit theory. Such a concrete subject that achieves this purpose can be summarized in three points: 1) How well do organizational culture, principal's values, and principal-organization values fit? And how does the fit of principal-teacher values prescribe the principal's leadership? 2) Does this 'values fit' exerts a positive influence leading to positive impacts or negative impacts concerning the principal's leadership? Is the values fit unrelated to the principal's leadership? And 3) What kinds of values prescribe the principal's leadership? The survey target was 995 teachers in 172 elementary schools for the Kyushu area, excluding Okinawa. The survey was conducted from October through December of 2002. 493 teachers participated in the survey with 136 principals. The return rate was 49.55% for the teachers survey and 79.07%. for the principal's survey. Fifteen variables were used on the occasion of analysis. The principal's leadership is composed of "transformational school leadership," "instructional leadership," and "fairness leadership." The organizational culture and the principal's values are composed of "creativity," "work environment," "autonomy," "collegiality," and "disciplinary" individually. We set up a person-organization (principal-organizational culture) fit and a person-person (principal-teacher) fit as the matching guidelines. As a result of analysis, we learned the following. First, the prescriptive factors of the principal's leadership were organizational culture and values fit (P-O fit and P-P fit). Yet, the biggest prescriptive factor of the principal's leadership was the organizational culture. In cases where it controlled the organizational culture, the values fit explained 2.5% of dispersion of the principal's leadership. Second, the values fit exerted a positive influence on the principal's leadership. The principal's values do not exert a direct influence on the principal's leadership. However, the principal's values have an effect that promotes leadership in cases where there was a match with the organizational culture or the teacher's values. Third, about 30% of the principal's leadership is explained by the organizational culture. In the organizational culture, the strong influence of "work environment" and "autonomy" to a principal's leadership were admitted. This shows that the principal who is succeeding in stress management is acknowledged as a leader.